Neolignans from the seeds of Myristica fragrans Houtt. - Van Cong, Pham; Hieu, Ngo Van; Duc, Ngo Viet; Ha, Pham Thuy; Tuan, Do Thanh; Hien, Nguyen Thi Thu; Anh, Hoang Le Tuan (Vietnam Journal of Science and Technology, 2022)
Myristica fragrans Houtt. is an aromatic evergreen tree that belongs to the Myristicaceae family. The seeds of this plant have been widely used in culinary field as a spice and in folk medicine for treating several diseases such as stomachic, stimulant, carminative, intestinal catarrh and colic, headaches, and diarrhea, and so on. In this study, seven neolignans including one new, maceneolignan L (1), and six known neolignans: erythro-(7S,8R)-∆8ʹ-4,7-dihydroxy-3,3',5'-trimethoxy-8-O-4'-neolignan (2), rhaphidecursinol B (3), maceneolignan H (4), maceneolignan F (5), (+)-(4-hydroxy-3-methoxy-1'-allyl-3',5'-dimethoxy)-8-O-4'-neolignan (6), (±) licarin A (7) were isolated from the seeds of M. fragrans Houtt. The structures of the compounds were determined by comprehensive spectroscopic analyses of their 1D-, 2D- NMR and high-resolution mass spectrometry (HR-EI-MS).